Cobalt catalyst performance in a water splitting photocatalytic dye sensitized photelectrochemical cell - Ng, Wei Jian. (2011)
The aim of the project was to find out the effectiveness of a cobalt-phosphate water oxidation catalyst (Co-Pi) in a dye-sensitized based photocatalytic water splitting cell. Co-Pi was electrodeposited onto ruthenium-based dye sensitized titanium dioxide (TiO2) photoanodes. The photoelectrochemical properties of the resulting composite photoanodes were measured using a linear sweep voltammetry method under front-side illumination in pH 7 electrolytes. The onset potential was shifted to a lower value but the plateau current was not observed in the resulting photocurrent graphs. This could be solved by decreasing the amount of Co-Pi deposited, changing the electrolyte to pH 13.6 NaOH and decreasing the thickness of TiO2 film. Co-Pi holds great potential to be an effective water oxidation catalyst in solar water splitting cells and improvement in the efficiency of dye-sensitized based photocatalytic water splitting systems is required in order to compete with more matured photovoltaic water splitting systems. Future prospects of solar water splitting systems include inserting a fast mediator between the water oxidation catalyst and the dye sensitizer to increase the turnover numbers and designing nanostructures that add the photovoltages in series at the liquid junction solar cells.